High body-mass index is not associated with worse clinicopathological characteristics in predominantly obese breast cancer patients - Kemal, Y.; Demirag, G.; Teker, F.; Kut, E.; Kefeli, M.; Ekiz, K.; Yucel, I. (Experimental Oncology, 2015)
Background: Breast cancer (BC) is the most common cancer among women. A high body-mass index (BMI) is related to increased incidence of BC with poorer prognosis. Aim: The aim of the study was to evaluate the association in patients with BC between BMI at the time of diagnosis and biological characteristics, according to the menopausal status. Materials and Methods: This retrospective study comprised a total of 318 women with BC. Clinicopathological differences between normal, overweight and obese patients according to menopausal status were evaluated. Results: Premenopausal women had a significantly lower BMI than postmenopausal patients (28.7 vs. 31.5, respectively; p = 0.00001). No statistically significant association was determined between BMI and clinicopathological characteristics in either the premenopausal or the postmenopausal group (all p values are > 0.05). Conclusions: There are many conflicting results in literature on this relationship. The results of this study showed that a high BMI is not associated with worse clinicopathological characteristics in a predominantly obese population. In current medical oncology practice, BC should be evaluated on an individual patient basis and the impact of obesity on BC prognosis seems to be difficult to estimate especially in an obese population. Key Words: breast cancer, body-mass index, prognosis.